The Effect of Liquidity, Solvency, and Profitability Ratios on Transportation Sub-Sector Companies Listed on The Bei in 2017-2021 - Aprilianti Maharani; Endah Dewi Purnamasari; Meilin Veronica (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyse the effect of liquidity, solvency, and profitability ratios on financial distress. The object of this research is transportation companies listed on the Indonesia Stock Exchange in 2017-2021. This type of research uses quantitative data research. The method used to measure financial distress is using the Altman Z-Score. The data analysis method uses multiple linear regression analysis with data processing using SPSS 24. The results showed that the liquidity variable had a positive effect on financial distress. Solvency variables have no effect on financial distress. Profitability has a positive effect on financial distress Liquidity, solvency, and profitability affect financial distress